A Validation Study of Heart Rate Variability Index in Monitoring Basketball Training Load - Jin, Naijing; Tian, Jie; Li, Yue; Mi, Jing (Frontiers in Physiology, 2022)
This study aimed to investigate whether the heart rate variability index (TLHRV) during five ball-drills could be used to quantify training load (TL) in collegiate basketball players. Ten elite male college basketball athletes (18.2 ± 0.4 years) were recruited to perform five ball-drills (1V1, 2V2, 3V3, 4V4, and 5V5) which lasted 10 min and varied in intensity. During each drill, TLHRV, training impulse (TRIMP), rating of perceived exertion (RPE), speed, and distance were recorded by Firstbeat, Foster’s RPE scale, and SiMi Scout. The correlation (Spearman’s and Pearson’s correlation coefficient), reliability (intra-class correlation coefficient, ICC), and agreement (Bland-Altman plots) among TLHRV, TRIMP, RPE, speed, and distance were examined. TLHRV was significantly correlated with TRIMP (r = 0.34, p = 0.015) and RPE (r = 0.42, p = 0.002). TLHRV was significantly correlated with training intensity (r = 0.477, p = 0.006) but not with volume (r = 0.272, p = 0.056). TLHRV and TRIMP, RPE showed significant intraclass relationships (ICC = 0.592, p = 0.0003). Moreover, TLHRV differentiated basketball drills of equal volume and varying intensity. We concluded that TLHRVmay serve as an objective and rational measure to monitor TL in basketball players.